Reliability of MRI Detection of Kaplan Fiber Injury in Pediatric and Adolescent Patients with ACL Tears. Issue 10 (25th October 2022) - Shi, Brendan Y.; Levine, Benjamin; Ghazikhanian, Varand; Bugarin, Amador; Schroeder, Grant; Wu, Shannon; Kremen, Thomas; Jones, Kristofer
Background: While studies have described Kaplan fiber (KF) injury in up to 60% of adults with anterior cruciate ligament (ACL) tears, the incidence of KF injury in the pediatric and adolescent population remains unknown. Purpose: To (1) determine the reliability of using magnetic resonance imaging (MRI) to identify KF injury in the pediatric and adolescent population and (2) define the incidence of KF injury in these patients with acute ACL injuries. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: The authors retrospectively identified patients ≤18 years of age who underwent ACL reconstruction for acute tears between 2013 and 2020. All preoperative MRI scans were reviewed independently and in a blinded fashion by 2 musculoskeletal radiologists, who noted the presence of the KF complex and any evidence of injury; interrater reliability was assessed. Patient characteristics, time from injury to MRI, laterality, and concomitant ligamentous or meniscal injuries were recorded, and associations between patient or injury characteristics and KF integrity on MRI were assessed. Results: In total, 51 patients (mean age, 14.9 years) met the inclusion criteria. Of these, 27 patients were female and 31 sustained an injury to the right knee. With respect to KF integrity, radiologist 1 visualized KF injury in 29% of patients, while radiologist 2 visualized KF injury in 35% of patients. In 12% of cases for radiologist 1 and 6% of cases for radiologist 2, KFs were unable to be visualized at all. The overall percentage agreement between the 2 radiologists was 76.5% with a kappa statistic of 0.57 (moderate agreement). There were no significant associations found between the presence of KF injury and patient age, sex, laterality, body mass index, concomitant ligamentous injury, or meniscal injury. However, visualization of KF injury on MRI was associated with a shorter time from index injury to MRI (15 days vs 23 days; P = .044). Conclusion: Approximately one-third of pediatric and adolescent patients who underwent ACL reconstruction were found to have KF injuries. Standard preoperative MRI scans can reliably be used to visualize KF injury in the majority of pediatric and adolescent patients with ACL tears, especially when the MRI is performed in the acute setting.